The Significance of State Practises in Enforcing the Principle of Effectiveness in Claims of Territorial Ownership - Vinata, Ria; Ibnu Asqori Pohan (Universitas Muhammadiyah Surabaya, 2023)
The state can obtain rights to a territory through various means of ownership, including prescription, accretion, cession, conquest, and occupation, as long as it can effectively control (occupation) the territory with long-lasting control (practical work). The Sipadan and Ligitan Islands dispute is Indonesia's first experience with the concept of effectivity. Effective control over an area dramatically influences the claim to ownership. Several countries claim land ownership based on ratio decidendi analysis of international court decisions. The Research method in this writing uses normative juridical analysis also known as the library research method. The author chose this approach because the analysis results will be discussed and explained concerning international law case studies. This research aims to analyze and describe the Role of State Practices in Implementing the Principle of Effectiveness towards Claims of Territorial Ownership.